Subject-Verb Agreement Errors in The Narrative Writing of The First Semester of English Literature Students: A Case Study - Lisbeth Sirait (Prodi Sastra Inggris UKI, 2022)
Abstract This study aimed at identifying the subject-verb agreement errors in 15 students’ narrative writing of the first semester of English literature. Descriptive qualitative method was used in conducting this study. The data of the study were collected through the use of The Pear Film as the instrument. The data obtained through the instrument were analyzed by classifying the errors into rules of Subject Verb Agreement(SVA) proposed by Azar (2003). The result of data analysis showed that error on the singular subject takes singular verb was 35 sentences. It was followed by plural subject takes a plural verb 6 sentences, sometimes phrases come between a subject and a verb. These phrases do not affect the agreement of the subject and verb 3 sentences, There + be + subject 3 sentences and collective nouns 2 sentences. Based on these findings, it is suggested to the teachers of English to use many various teaching methodologies to help the students understand the SVA rules and apply them in their studies. Key words: subject verb agreement, error, narrative, writing.